D‐512, a novel dopamine D2/3 receptor agonist, demonstrates greater anti‐Parkinsonian efficacy than ropinirole in Parkinsonian rats. (11th August 2017) - Lindenbach, David; Das, Banibrata; Conti, Melissa M; Meadows, Samantha M; Dutta, Aloke K; Bishop, Christopher
Abstract : Background and Purpose: Symptoms of Parkinson's disease are commonly managed using selective dopamine D2/3 receptor agonists, including ropinirole. While D2/3 agonists are useful in early‐stage Parkinson's disease, they tend to lose efficacy in later disease stages and do not appear to modify disease progression. We have recently developed a novel 'multifunctional' compound, D‐512: a high‐affinity D2/3 receptor agonist with antioxidant and other neuroprotective properties that may limit Parkinson's disease progression. This study sought to compare the anti‐Parkinsonian properties of the clinically used compound, ropinirole, with those of the novel compound, D‐512. Experimental Approach: A rat model of Parkinson's disease was created by unilaterally infusing 6‐hydroxydopamine, a dopamine neurotoxin, into the medial forebrain bundle. D‐512 was compared with ropinirole for ability to stimulate spontaneous motor activity and reverse Parkinsonian akinesia. These beneficial effects were compared against each drug's liability to provoke dyskinesia, a common motor side effect. Key Results: Both compounds increased spontaneous movement, but D‐512 showed a longer duration of action. Only D‐512 was able to significantly reverse forelimb akinesia. Drug‐induced dyskinesia was similar for equivalent doses. Conclusions and Implications: Compared with ropinirole, D‐512 showed greater peak‐dose efficacy and a longer duration of action, despite a similar side‐effect profile. Our results add to earlier data showing that D‐512 is superior to available D2/3 agonists and could merit clinical investigation.